COORDINATION OF APPARATUS IN THE MANAGEMENT OF POPULATION ADMINISTRATION IN MONANO DISTRICT, NORTH GORONTALO REGENCY - Mohi, Widya Kurniati; Tahir, Arifin (Universitas Negeri Gorontalo, 2022)
The purpose of this study was to find out and obtain an objective picture of the coordination of the apparatus in the management of population administration and to determine the supporting and inhibiting factors for carrying out the coordination of the Monano sub-district office apparatus, North Gorontalo Regency. The results showed that the apparatus in managing the coordination of the apparatus in the management of population administration at the Monano subdistrict office, coordinating activity planning, coordination of the implementation of activities and coordination of evaluation of activities in general has been arranged, but in particular the coordination of planning management and evaluation of population administration management activities has not been maximized, this can be seen from the lack of coordination of administrative management planning, both long term and medium term and short term, especially at the Monano sub-district office. alone. The supporting factor in achieving the success of population administration at the Monano sub-district office is the loyalty and cooperation of all components and human resources involved in the service process.